Case Report: Bacterial meningitis due to cerebrospinal fluid leakage following unilateral biportal endoscopic spinal surgery: a cautionary tale - Wang, Haoyu; Wang, Yunhui; Jiang, Zhensong; Zhang, Wen (Frontiers in Surgery, 2024)
In this report, we present a case of bacterial meningitis (BM) due to dural tears in unilateral biportal endoscopic spinal surgery (UBE) surgery and its treatment and prevention. We reported a 47-year-old man with cerebrospinal fluid (CSF) due to an intraoperative dural tear. A drainage tube was routinely placed and removed on the 4th postoperative day, resulting in fever and headache on the afternoon of the day after the drainage tube was removed. Blood and CSF cultures resulted in Klebsiella pneumoniae infection, and with lumbar drainage and appropriate antibiotics based on sensitivity testing, the patient's fever and headache were effectively relieved. This case report suggests the importance of prolonged drainage tube placement, adequate drainage, careful intraoperative separation to avoid dural tears, and effective sensitive antibiotic therapy. In recent years UBE has attracted great interest among spine surgeons, and to our knowledge, there have been no reports of BM caused by CSF leakage after UBE surgery. Our case study introduces the pathogenesis of BM and its' related treatment and preventive measures, which may fit the scope of the journal and the research topic of "Bacterial Meningitis: Epidemiology, Pathogenesis and Beyond". Thank you very much.